2016
DOI: 10.1007/s13277-016-5295-4
|View full text |Cite
|
Sign up to set email alerts
|

MiR-377 inhibits the proliferation of pancreatic cancer by targeting Pim-3

Abstract: MicroRNAs (miRNAs) play important roles in the regulation of various tumor biological processes including proliferation and apoptosis. MiR-377 has been implicated in many types of cancer, whereas its expressional feature and potential biological function in pancreatic ductal adenocarcinoma (PDAC) remains unclear. In this study, we scanned the global miRNA expression profiles in PDAC from The Cancer Genome Atlas (TCGA) and found miR-377 was down-regulated significantly in PDAC. Then, its expression was measured… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 45 publications
1
32
0
Order By: Relevance
“…3,6 MicroRNAs (miRs) have been found to be promising regulators of gene expression in various biological and pathologic processes of tumors, including carcinogenesis, tumor growth, tumor differentiation, carcinoma metastasis, cancer apoptosis, and epithelial-mesenchymal transition (EMT). 7,8 Evidence has demonstrated that miRs act as either tumor suppressors or oncogenes by interfering in the basepairing with target mRNA and altering various signaling pathways associated with the disease. 9 MiR-300, a member of the miRNA family, localizes in the Dlk1-Dio3 microRNA cluster, region 14q32.31.…”
Section: Introductionmentioning
confidence: 99%
“…3,6 MicroRNAs (miRs) have been found to be promising regulators of gene expression in various biological and pathologic processes of tumors, including carcinogenesis, tumor growth, tumor differentiation, carcinoma metastasis, cancer apoptosis, and epithelial-mesenchymal transition (EMT). 7,8 Evidence has demonstrated that miRs act as either tumor suppressors or oncogenes by interfering in the basepairing with target mRNA and altering various signaling pathways associated with the disease. 9 MiR-300, a member of the miRNA family, localizes in the Dlk1-Dio3 microRNA cluster, region 14q32.31.…”
Section: Introductionmentioning
confidence: 99%
“…Accumulating evidence shows that miRNA are involved in tumorigenesis and metastasis of various human cancers, including HPAC . Furthermore, miRNA have been implicated to function as both tumorigenic or tumor‐suppressing genes .…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidence shows that miRNA are involved in tumorigenesis and metastasis of various human cancers, including HPAC. (21)(22)(23) Furthermore, miRNA have been implicated to function as both tumorigenic or tumor-suppressing genes. (11) The overexpression of miR-372 in some cancers (24,25) has been reported to play an oncogenic role.…”
Section: Discussionmentioning
confidence: 99%
“…Two miRNAs (miR-374a-3p, miR-340-5p) have yet to be associated with pancreatic cancer but involved in other types of cancer [20,21]. Furthermore, of the top 10 miRNAs down-regulated in spheroids, five miRNAs (miR-486-3p, miR-134-5p, miR-320a, miR-127-3p, and miR-377-3p) have been reported previously to be related to pancreatic cancer, and three of them were found playing an important role in drug resistance (miR320a) [22], cell proliferation (miR-377-3p) [23], or as a tumor suppressor (miR-127-3p) [24],while the other two miRNAs had no further study yet. Four miRNAs, miR-370-3p, miR-185-5p, miR-193a-5p and miR-378a-3p were all associated with chemoresistance and involved in other types of cancer [25][26][27][28].…”
Section: Panc-1 Spheroid Cells Have Higher Tumorigenic Potential In Vivomentioning
confidence: 97%